(untitled) (Medicine Today, 2017)
Early diagnosis of acute appendicitis in children is a challenge for the pediatric surgeons. The objectives of this study were to compare the accuracy of Modified Alvardo Score (MAS) & Pediatric appendicitis Score (PAS) in the management of acute appendicitis in children, to make early diagnosis & treatment of acute appendicitis and to reduce morbidity of negative appendectomy or delayed appendectomy. It was a comparative prospective study. This study was carried out in Dhaka Shishu (Children) Hospital from January’ 2004 to April ’2005, a period of 16 months in the department of Pediatric Surgery. During this 16 months period, 106 patients with suspected acute appendicitis were admitted. Among these, 97 patients underwent surgery and 9 patients treated conservatively. Out of 97 patients, 90 specimens were sent for histological examination. Positive histological (Positive appendix) criteria of acute appendicitis required demonstration of acute inflammatory cells infiltration of the appendix wall. Only 85 histological reports were available finally & were included in this study. The sensitivity, specificity and diagnostic accuracy of MAS are 92.42%, 84.21% & 90.59% respectively. The sensitivity, specificity and diagnostic accuracy of PAS are 90.91%, 100% & 92.94% respectively. In these two scoring systems, the sensitivity, specificity and diagnostic accuracy are high. But in our study, PAS is better than the MAS regarding specificity & diagnostic accuracy. Medicine Today 2017 Vol.29(1): 19-22